Progressive Islamic Law and Misek Tradition of Dayak Ngaju in Central Kalimantan - Sadiani, Sadiani; Emzaed, Ali Murtadho; Amin, Muhammad; Mualimin, Mualimin; Rosadhillah, Valencia Kirana (El-Mashlahah, 2023)
Misek tradition is known as the proposing procession of the Dayak Ngaju community in Central Kalimantan before marriage. This tradition is still preserved by the indigenous people, even though they have converted to Islam. As a law that lives in society, misek has become the nation's cultural heritage and, at the same time, enriches the national cultural treasures of Indonesia. The presence of Islam in the lives of the Dayak Ngaju community did not immediately eradicate the misek tradition. Progressive Islamic law has an elastic accommodation to adapt misek cultural values. This research aimed to analyze the progressive Islamic law and misek tradition of the Dyak Ngaju Community in Central Kalimantan. The research was empirical legal research, with data sources from observation, interviews, and documentation. Accommodation theory is used for the research. The research showed two conclusions. First, Misek's traditional practice has two processes, namely the misek hakumbang auh process (the small proposal procession) and the misek hakumbang hai (the big proposal procession). Second, progressive Islamic law accommodates the cultural values of misek, both misek hakumbang auh and misek hakumbang hai as good customs. The Misek tradition can coexist with Islamic law without losing its traditional identity.